Comparative Evaluation of heat-inactivated ABO isoagglutinin titers with solid-phase red cell adhesion titers - Shweta Ranjan; Prashant Pandey; Divya Setya; Supriya Kumari (Global Journal of Transfusion Medicine, 2022)
Background and Objectives: Measurement of actual concentration of IgG requires methods like heat inactivation (HI) of serum. This study was aimed at comparing of heat-treated ABO titers performed by conventional test tube technique (CTT) and column agglutination technique (CAT) with hemagglutination (HA)/solid-phase red cell adherence (SPRCA). Methods: This was a prospective, observational study conducted between October 2019 and March 2020. All consecutive A, B, and O group donors who gave consent for participation in the project were included. All samples were tested by CTT and CAT before and after HI (post DTT treatment performed by CTT [pCTT] and post DTT treatment performed by CAT [pCAT]) and with HA/SPRCA. Results: A total of 300 donors were included: 100 each with A, B, and O blood groups. For group O, IgG titers were higher than IgM titers among group O, whereas that among group A and group B, IgM titer was found to be higher than IgG titer by both HA/SPRCA and pCTT. The titer values among all the three blood groups were highest when the test was performed by pCAT, though the results of pCTT and SPRCA, pCTT, and pCAT were significant in group O donors. For groups A and B, results of pCTT and pCAT, pCAT, and HA/SPRCA were found to be statistically significant. Conclusion: Results obtained by HA/SPRCA were closer to pCTT, with respect to time consumption, expertise required, and lack of inter-observer variation. Titers obtained by pCAT were higher in comparison to pCTT obviously due to its relative higher sensitivity. Hence, these methods cannot be used interchangeably.